The canning quality of Philippine oranges (Ladu and King varieties) - Peleo, Teresita Ochoa 1940- (1961)
The possibility of canning native varieties of orange, Ladu and King is determined with a view of determining their canning qualities. The study notes that with different varieties of orange, slightly different treatments are necessary in order for the canning quality to be generally acceptable.